Pengaruh pencampuran minyak ikan nila, stearin sawit, dan minyak biji karet terhadap karakteristik fisikokimia biskuit: The effect of blending tilapia fish oil, palm stearin, and rubber seed oil on the physicochemical characteristics of biscuits - Sumartini, Sumartini; Hasibuan, Nirmala Efri; Pamaharyani, Luchiandini Ika; Saputra, Eko Novi; Suryono, Muhamad; Azka, Aulia; Ratrinia, Putri Wening; Basri, Basri (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Biscuits are made from a mixture of ingredients and shortening. The type of fat used affects the quality of the biscuits. Rubber seed waste, bones, heads, scales, skin, and entrails of fish are plantation and fishery wastes that can be used to make fat as a raw material for shortening. This study aimed to determine the best ratio of shortening palm stearin, fish oil, and rubber seed oil, which is neutralized and deodorized with a solid ratio, to the physical properties and texture of the dough. Completely Randomized Design (CRD) was used with 5 treatments (palm stearin/rubber seed oil/fish oil): ratio 1 (50:30:20), ratio 2 (60:35:5), ratio 3 (70:15:15), ratio 4 (80:10:10), and ratio 5 (90:5:5). The test parameters included diameter, hardness, thickness, texture, color, water content, protein, fat, calories, and sensory properties. Data analysis was performed using SPSS Version 25 with a 95% ANOVA. The results obtained were as follows: lightness of biskuits 74.57-78.55; thickness 0.54-0.94 mm; diameter 90.38-110.16 mm; hardness 2769.36-3648.53 g; fat content 18.61-20.64%; protein 10.38-10.88%; calorific value 623,680-625,367 kcal. The highest sensory testing results were at ratio 4 (80: 10: 10). The correct proportion of shortening ratio influences the physical and chemical characteristics of the biskuits produced, where the best ratio is 80: 10: 10.